EFEKTIVITAS PEMBERIAN INHALASI GINGER ESSENTIAL OIL TERHADAP FREKUENSI MUAL DAN MUNTAH PADA IBU HAMIL DENGAN EMESIS GRAVIDARUM TRIMESTER I DI RUMAH SAKIT ‘AISYIYAH KUDUS - Ayu Siti Sundari; Islami; Indah Puspitasari (Jurnal Medicare, 2026)
Nausea and vomiting during pregnancy are among the most common complaints experienced by pregnant women. One form of non-pharmacological therapy that can be used is ginger aromatherapy. This study aims to determine the effectiveness of ginger essential oil inhalation on the frequency of nausea and vomiting in pregnant women with first trimester emesis gravidarum at 'Aisyiyah Kudus Hospital. This study was categorised as an experimental study with one experimental group. The population in this study was all pregnant women experiencing emesis gravidarum. During the research period in September 2025, there were 60 respondents. The sample size was calculated using the Slovin formula, which yielded 52 respondents. The research instrument used was the PUQE 24. The data were analysed using the Wilcoxon test. The results of this study showed that before being given ginger essential oil inhalation, most respondents experienced moderate nausea and vomiting, numbering 35 (67.4%) respondents. After being given the inhalation, most respondents did not experience nausea and vomiting, numbering 22 (42.3%) respondents. There was an effectiveness of ginger essential oil inhalation on the frequency of nausea and vomiting in pregnant women with first trimester emesis gravidarum at 'Aisyiyah Kudus Hospital with a p-value of 0.000 < 0.05.